Nitric Oxide (NO) and Cancer Prognosis, Prevention, and Therapy - Bonavida, Benjamin; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2010)
The Nobel Prize in Physiology and Medicine was awarded in 1998 to Doctors Furchgott, Ignarro, and Murad for their discoveries concerning "Nitric oxide (NO) as a signaling molecule in the cardiovascular system." NO-inducing cell signaling events within the cell producing it and the diffusibility to NO in other cells have led to the discovery of many other physiological functions in many different types of cells including cancer. Noteworthy, nitroglycerin that has been used for the treatment of chest pain and associated cardiovascular diseases is currently being investigated for its therapeutic effect in clinical studies in patients with cancer. Further, several NO donor compounds have shown, in preclinical studies, anti-tumoral chemopreventive and therapeutic activities. "Nitric Oxide and Cancer: Prognosis, Prevention and Therapy", edited by Benjamin Bonavida, Ph.D., reviews several novel applications of NO in cancer, a new field that has rapidly gained credibility and understanding at the biochemical and molecular levels. The various chapters in this comprehensive volume (25 contributions), written by noted experts in the field, bring up-to-date our current understanding and prospective future clinical applications of NO.
General Overview -- Nitric Oxide and Cancer: An Overview -- Nitric Oxide and the Pathogenesis of Cancer -- A Role for eNOS in Oncogenic Ras-Driven Cancer -- Dual Role of Nitric Oxide in Cancer Biology -- Nitric Oxide Expression in Cancer -- Dual Roles of Nitric Oxide in Protecting or Inducing Cell Death -- S-Nitrosylation – How Cancer Cells Say NO to Cell Death -- Cytotoxic and Protective Activity of Nitric Oxide in Cancers -- Cytotoxic/Protective Activity of Nitric Oxide in Cancer -- Nitric Oxide and Life or Death of Human Leukemia Cells -- Inhibition of Apoptosis by Endogenous Nitric Oxide in Chronic Lymphocytic Leukaemia -- Role of Nitric Oxide in Metastasis -- Nitric Oxide: A Rate-Limiting Factor for Metastases Development -- Nitric Oxide Inhibits Tumor Cell Metastasis via Dysregulation of the NF-?B/Snail/RKIP Loop -- Nitric Oxide as a Sensitizing Agent for Chem-Radio-Immunotherapy -- Sensitizing Effect of Nitric Oxide to Cytotoxic Stimuli -- Nitric Oxide Is a Promising Enhancer for Cancer Therapy -- Role of Nitric Oxide for Modulation of Cancer Therapy Resistance -- Breaking Resistance: Role of Nitric Oxide in the Sensitization of Cancer Cells to Chemo- and immunotherapy -- Prognostic Significance of NOS and NO -- Prognostic Significance of iNOS in Human Melanoma -- Prognostic Significance of iNOS in Hepatocellular Carcinoma -- Prognostic Significance of iNOS in Esophageal Cancer -- Prognostic Significance of Nitrative DNA Damage in Infection- and Inflammation-Related Carcinogenesis -- Therapeutic Applications of Nitric Oxide -- Nitric Oxide-Releasing Molecules for Cancer Therapy and Chemoprevention -- Nitric Oxide: Monotherapy or Sensitiser to Conventional Cancer Treatments? -- Therapeutic Applications of Nitric Oxide for Malignant Tumor in Animal Models and Human Studies -- (S,R)-3-Phenyl-4,5-dihydro-5-isoxazole acetic acid–Nitric Oxide (GIT-27NO) – New Dress for Nitric Oxide Mission -- Nitric Oxide Donors Are a New Class of Anti-cancer Therapeutics for the Reversal of Resistance and Inhibition of Metastasis -- Role of Inducible Nitric Oxide Synthase (iNOS) in Regulation of Nitric Oxide (NO) Production and Stabilization of HIF-1?: Potential Role of Se-Methylselenocysteine (MSC), an Antioxidant Multi-targeted Small Molecule.
Keywords: Cancer research; Oncology .; Pharmacology; Cancer Research; Oncology; Pharmacology/Toxicology.